Alternative Separation Process of Thermoplastic Polymer for Environmental Assessment - Altuwair , Ibrahim (Recent Progress in Science and Technology Vol. 6, 2023)
In this paper, traditional processing and alternative modified methods for polycarbonate production were described and compared in terms of Environmental Performance Evaluation (PEP) to identifying opportunities to improve environmental performance of polycarbonate production processes. Chemical industrial processes have become "business as usual," with their energy-intensive production techniques and unsavoury reputation. One example of an energy-intensive process that has grown to be one of the most important industrial processes is polycarbonate (PC). Additionally, numerous dangerous chemicals are employed throughout all phases of its production. Environmental evaluation consists of process description, hazard or chemical identification, scenario identification to measure the impact or severity and the probability of occurrence. The benefits of using SCF are related to the technology's cleaner aspects, minimization of raw material and energy consumption, reduction of emissions and effluent discharge into the environment, and maximisation of environmental benefits. Supercritical fluid safely improves EPP while also significantly reducing impurities. SCF's production of polycarbonates and conventional production techniques were compared for environmental performance. When compared to conventional methods, it was found that supercritical fluid technology has an effect on the reduction of emissions. The research aids in understanding the difficulties that the polycarbonate industry will encounter as chemical emissions rise as a result of increased production and energy use. A crucial and effective alternative tool is therefore needed.